O Lixo no Ambiente em que Vivemos II - Cunha , Clotildes Aparecida Feles da; Faquini , Josieli Loise de Queiros Silva; Alves, Joana Darc Xavier (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf